A Stylistic Study of Situational Elements in Selected American Creeds - Ayad Hameed Mahmoud; Alyaa Husein Abd Fatah (Hasanuddin University, 2023)
The study is intended to stylistically analyze a sample of three American military creeds. The study hypothesizes that American military creeds have their own stylistic properties which make them distinct texts, and that the stylistic devices employed in military creeds vary in terms of their frequencies and functions. The study also hypothesizes that military creeds are situationally based, and that the employed stylistic devices have a complementary role. They all contribute together to fulfill the creeds’ aims and convey their intended messages. To achieve the aims of the study, and verify its hypotheses, two types of procedure are followed: theoretical and practical. The theoretical part consists of presenting a theoretical framework of style and stylistics including their historical background, types, approaches, models of analysis, etc. Another theoretical framework is also presented about military discourse and creeds including their historical background, terminology, features, etc. On the other hand, the practical part consists of selecting a sample of three military creeds and analyzing them in the light of Crystal and Davy’s (1969) model which accounts for situational elements. The adopted model consists of five dimensions: individuality, discourse, status, modality, and singularity. The results of analysis show that military creeds have their own distinctive stylistic features. The results also show that the stylistic devices characterizing military creeds have a complementary role in that they all contribute together to achieve the creeds’ aims and convey their intended messages.